Tunable silencer for rectangular ventilation duct based on composite Helmholtz resonators - Gao Cong; Hu Chuandeng; Hou Bo; Wu Xiaoxiao; Wen Weijia (Acta Acustica, 2024)
To attenuate low-frequency noise in square ventilation ducts, a tunable duct silencer consisting of composite Helmholtz resonators (HR) that precisely controlled by a step motor was proposed in this paper. An analytical model based on temporal coupled mode theory (TCMT) is applied to explain the sound absorption mechanism. The design breaks the limitation that the operating frequency of a silencer is fixed after manufacturing and avoids the degradation of ventilation conditions by attaching to the duct as a side branch. By using a step motor to drive the tunable cavity HR, the silencer can achieve accurate and continuous adjustment of the operating frequency over the entire operating frequency spectrum. In the experiment, the silencer has an absorption bandwidth of 250 Hz and ranges from 710 Hz to 960 Hz. Porous material is inserted into the cavities of HR to improve the damping properties. When integrated into the simulation model, it enables the rapid design of silencer dimensions for different sound absorption frequencies. The design demonstrates a new solution for low frequency sound attenuation in ventilation ducts and provides a potential technique for the future development of active controlled duct silencers.